Explicit treatment of active-site waters enhances quantum mechanical/implicit solvent scoring: Inhibition of CDK2 by new pyrazolo[1,5-a]pyrimidines - Hylsová, Michaela; Carbain, Benoit; Fanfrlík, Jindřich; Musilová, Lenka; Haldar, Susanta; Köprülüoğlu, Cemal; Ajani, Haresh; Brahmkshatriya, Pathik S; Jorda, Radek; Kryštof, Vladimír; Hobza, Pavel; Echalier, Aude; et al. (European journal of medicinal chemistry, 2017)
We present comprehensive testing of solvent representation in quantum mechanics (QM)-based scoring of protein-ligand affinities. To this aim, we prepared 21 new inhibitors of cyclin-dependent kinase 2 (CDK2) with the pyrazolo[1,5-a]pyrimidine core, whose activities spanned three orders of magnitude. The crystal structure of a potent inhibitor bound to the active CDK2/cyclin A complex revealed that the biphenyl substituent at position 5 of the pyrazolo[1,5-a]pyrimidine scaffold was located in a previously unexplored pocket and that six water molecules resided in the active site. Using molecular dynamics, protein-ligand interactions and active-site water H-bond networks as well as thermodynamics were probed. Thereafter, all the inhibitors were scored by the QM approach utilizing the COSMO implicit solvent model. Such a standard treatment failed to produce a correlation with the experiment (R2 = 0.49). However, the addition of the active-site waters resulted in significant improvement (R2 = 0.68). The activities of the compounds could thus be interpreted by taking into account their specific noncovalent interactions with CDK2 and the active-site waters. In summary, using a combination of several experimental and theoretical approaches we demonstrate that the inclusion of explicit solvent effects enhance QM/COSMO scoring to produce a reliable structure-activity relationship with physical insights. More generally, this approach is envisioned to contribute to increased accuracy of the computational design of novel inhibitors.
Keywords: Catalytic Domain; Humans; inhibitory proteinkinas; pyrimidiny; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; X-ray crystal structure; Cyclin A; cyklin-dependentní kinasa 2; Solvents; Molecular dynamics; Cyclin-dependent kinase 2; lidé; cyklin A; Water thermodynamics; rozpouštědla; Drug Design; simulace molekulární dynamiky; Protein Kinase Inhibitors; Quantum Theory; Molecular Dynamics Simulation; katalytická doména; kvantová teorie; voda; racionální návrh léčiv; Pyrazolo[1,5-a]pyrimidine; Cyclin-Dependent Kinase 2; Protein-ligand binding; Water; Pyrimidines; Quantum mechanical scoring; ATP-competitive type I inhibitors